Expression and localisation of glucose transporter 1 (GLUT1) in dairy goat mammary gland at different physiological stages - Na, Z; Qingzhang, L; Xuejun, G; Xuemei, N; Hongbo, Y; Chun, L (Canadian journal of animal science, 2009)
Glucose is the major energy source for mammary epithelial cells, as well as an important substrate for lactose synthesis. Mammary epithelial cells take up glucose from extracellular fluid into the cell through glucose transporter (GLUT). This study was aimed at investigating the expression of GLUT1 glucose transporter in dairy goat mammary gland during puberty, pregnancy, lactation, and involution. Using real-time reverse transcription PCR (qRT-PCR) and Western blotting, we analyzed the expression of GLUT1 mRNA and protein in dairy goat mammary gland. GLUT1 mRNA and protein expression increased during pregnancy and lactation, especially at peak lactation, and decreased strongly after weaning. Furthermore, the location of GLUT1 protein was determined by immunofluorescence laser confocal microscopy. GLUT1 protein localised to the basal and apical plasma membrane of epithelial cells, and also in the cytoplasm. The results from this study showed that GLUT1 is expressed in the dairy goat mammary gland with the greatest expression found in mammary epithelial cells during pregnancy and lactation.